Validity of ICD-9-CM codes for breast, lung and colorectal cancers in three Italian administrative healthcare databases: a diagnostic accuracy study protocol. Issue 3 (25th March 2016) - Abraha, Iosief; Serraino, Diego; Giovannini, Gianni; Stracci, Fabrizio; Casucci, Paola; Alessandrini, Giuliana; Bidoli, Ettore; Chiari, Rita; Cirocchi, Roberto; De Giorgi, Marcello; Franchini, David; Vitale, Maria Francesca; et al.
Abstract : Introduction: Administrative healthcare databases are useful tools to study healthcare outcomes and to monitor the health status of a population. Patients with cancer can be identified through disease-specific codes, prescriptions and physician claims, but prior validation is required to achieve an accurate case definition. The objective of this protocol is to assess the accuracy of International Classification of Diseases Ninth Revision—Clinical Modification (ICD-9-CM) codes for breast, lung and colorectal cancers in identifying patients diagnosed with the relative disease in three Italian administrative databases. Methods and analysis: Data from the administrative databases of Umbria Region (910 000 residents), Local Health Unit 3 of Napoli (1 170 000 residents) and Friuli-Venezia Giulia Region (1 227 000 residents) will be considered. In each administrative database, patients with the first occurrence of diagnosis of breast, lung or colorectal cancer between 2012 and 2014 will be identified using the following groups of ICD-9-CM codes in primary position: (1) 233.0 and (2) 174.x for breast cancer; (3) 162.x for lung cancer; (4) 153.x for colon cancer and (5) 154.0–154.1 and 154.8 for rectal cancer. Only incident cases will be considered, that is, excluding cases that have the same diagnosis in the 5 years (2007–2011) before the period of interest. A random sample of cases and non-cases will be selected from each administrative database and the corresponding medical charts will be assessed for validation by pairs of trained, independent reviewers. Case ascertainment within the medical charts will be based on (1) the presence of a primary nodular lesion in the breast, lung or colon–rectum, documented with imaging or endoscopy and (2) a cytological or histological documentation of cancer from a primary or metastatic site. Sensitivity and specificity with 95% CIs will be calculated. Dissemination: Study results will be disseminated widely through peer-reviewed publications and presentations at national and international conferences.